Toward mapping potential groundwater recharge zones across Viti Levu and Vanua Levu (Fiji islands) - Vilimone Koiroko Raqona; Shailesh Kumar Singh; Ude Shankar (Sustainable Earth Trends)
Water access in Fiji is a critical issue as not everyone can access reticulated water sources which poses heavy dependence on groundwater sources. Along with its various uses, groundwater sources have been left vulnerable to contamination and depletion over the years due to changes in climatic patterns and human influence. Traditional hydrometric groundwater survey is performed monthly to help determine recharge potential areas in Fiji but doesn’t cover all the water sources nor considers all the factors contributing to groundwater recharge. GIS, presents a contemporary approach to identify potential recharge areas which has been used in this study. In this study, the Multi Influencing Factor technique was used to determine the weightage of the factors aspect, slope, soil drainage, drainage density, parent materials and rainfall which are believed to have potentially contribute to groundwater recharge.  The basic GIS tools of overlaying and reclassification was used to denote the relationships between the factors and groundwater recharge and the potential groundwater recharges areas for Viti Levu and Vanua Levu.  Results have shown that higher potential areas are mostly areas with lower altitudes such as plains, wet areas (windward side), water bodies, excessively drained soils and parent materials with high exposure to weathering. Low ground water recharge potential areas are mostly mountainous, poorly drained soils, dense vegetation and poorly permeable bedrocks. These information is compared against existing boreholes and findings are to assist the government to invest more in those areas that have high recharge areas.